2004
DOI: 10.1097/01.hjr.0000116826.84388.30
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of ventricular arrhythmia modified by ability to adapt to stressful situations

Abstract: A maladaptive behaviour in a stressful encounter makes men with electrocardiographically detected ventricular arrhythmias more vulnerable and thereby exposed to an increased risk of a future myocardial infarction and overall mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…An association between sAA activity and autonomic cardiovascular parameters has been reported in healthy subjects in response to physical as well as psychological stressors 13. Furthermore, exercise,24 and smoking,25 as well as psychological factors known to stimulate sAA activity such as anger,26 anxiety, phobic anxiety27 and maladaptive behaviour in stressful encounters,28 have been shown to be associated with the risk of VA or SCD, providing a theoretical basis for the use of the sAA assay.…”
Section: Discussionmentioning
confidence: 98%
“…An association between sAA activity and autonomic cardiovascular parameters has been reported in healthy subjects in response to physical as well as psychological stressors 13. Furthermore, exercise,24 and smoking,25 as well as psychological factors known to stimulate sAA activity such as anger,26 anxiety, phobic anxiety27 and maladaptive behaviour in stressful encounters,28 have been shown to be associated with the risk of VA or SCD, providing a theoretical basis for the use of the sAA assay.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, it may modify the effect of risk factors. A recent study showed that the effect of ventricular arrhythmia on prognosis was absent in those with good ability for tension regulation [48]. We need new studies not only to replicate the result and estimate effect size more accurately, but also to obtain information on the possible pathways of such an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviors categorized as adaptive show stable or increasing time consumption throughout the test but do not show recurrent declines and increases in time consumption. The Variability-dimension was chosen for the present study because its associations with increased incidence of MI in men [ 10 , 12 , 13 ]. All categorization of behavior in this study is based on comparisons of test scores with reference-medians obtained from the 180 patients that were able to participate in the CWT in the SECAMI-study.…”
Section: Methodsmentioning
confidence: 99%
“…Hypertensive men who many years in advance of a clinical event had difficulties to adapt to the stressful test were exposed to an increased risk of a myocardial infarction (MI) [ 10 ] or stroke [ 11 ]. Ventricular arrhythmia [ 12 ] and asymptomatic atherosclerosis [ 13 ] were less important predictors among the men who managed to handle the stressful task in an adaptive manner. Postinfarction mortality within 28 days and within one year could also be explained by behavior in the serial CWT [ 14 ].…”
Section: Introductionmentioning
confidence: 99%